Collateral circulation alters downstream hemodynamic stress caused by intracranial atherosclerotic stenosis. (3rd June 2017) - Liu, Xin; Dornbos, David; Pu, Yuehua; Leng, Xinyi; Song, Ligang; Jia, Baixue; Pan, Yuesong; Wang, David; Miao, Zhongrong; Wang, Yilong; Liu, Liping; Wang, Yongjun
Abstract: Objectives: Fractional flow reserve (FFR) accurately predicts the degree of stenosis and is now widely used to identify clinically significant severe coronary artery lesions. In the current study, we utilized a similar indicator, fractional flow (FF), to determine the hemodynamic impact of symptomatic intracranial atherosclerotic stenosis (ICAS) and to assess the correlation of FF with the severity of stenosis and collateral circulation. Methods: Patients with symptomatic ICAS (70–99% stenosis) confirmed on digital subtraction angiography (DSA) were consecutively recruited. FF was obtained during DSA examination with the use of pressure sensors and was measured as a ratio, comparing measurements distal to an ICAS lesion (Pd) and within the aorta (Pa). The degree of leptomeningeal collateralization was graded from zero (absent) to four (complete compensatory). The correlation between FF, anatomical stenosis, and collateral status was then analyzed. Results: Twenty-five patients with a mean age of 55.6 years were analyzed. The median percentage of stenosis and median FF were 82.3 and 0.68%, respectively. Eleven patients were found to have poor collateralization (grade 0-2), and fourteen patients were identified with good collateral circulation (grade 3-4). Overall, the hemodynamic impact of an atherosclerotic lesions worsened (decreased FF) as the percentage of stenosis increased, although this did not reach statistical significance ( r  = −0.398, p  = 0.06). However, the status of collateralization significantly altered this correlation, worsening the hemodynamic impact in patients with poor collateral circulation ( r  = −0.677, p  = 0.032). There was no difference in patients with good collateral circulation ( r  = −0.279, p  = 0.356). Conclusion: An anatomically severe (70–99%) symptomatic ICAS lesion may generate significant hemodynamic stress downstream as assessed by the indicator FF, particularly in patients with poor collateral circulation. Further, good collateralization may mitigate this hemodynamic impact, partially explaining the protective effect of collateral circulation against recurrent stroke in such patients.